(untitled) (Journal of the College of Basic Education, 2023)
Al-Sayyab.. a view of his critical references:Literature in Iraq continued to pursue all events, keep pace with them, and record them in poetry, prose, and proverbs.An Arab cry in the face of the colonialists and a launch towards renewal and modernization, especially since the history of IraqThe Arab world is full of political and literary events.As the forties of the twentieth century approached, the features of the poetic renaissance emerged.hadith as a result of well-known political, literary, social and intellectual repercussions.Studying the motives and motives of the literary renaissance, they must point to one of its main pillars.He is Badr Shaker Al-Sayyab, who presented a successful experiment, and got out of the traditional framework in buildingThe Arabic poem.